2023
DOI: 10.1002/admi.202202062
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Driven Superlubricity of Graphene/Graphene in Commensurate Contact

Abstract: The occurrence of structural superlubricity (SSL) requires that two sliding surfaces be in incommensurate contact. However, the incommensurate contact between two sliding surfaces is fundamentally an instable state whose maintenance over time is extremely laborious. To circumvent this difficulty, it is proposed in the present work to change the paradigm of making appear superlubricity and keeping it over time. Two graphene layers in sliding commensurate contact, which are subjected to an isotropic in‐plane syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Recent studies have shown that by manipulating the alignment of graphene layers, superlubricity can be achieved. Cheng et al [ 39 ] demonstrated that two graphene layers in sliding commensurate contact, which are subjected to an isotropic, in-plane, synchronous strain, induce superlubric behavior.…”
Section: Mechanics Of Superlubricitymentioning
confidence: 99%
“…Recent studies have shown that by manipulating the alignment of graphene layers, superlubricity can be achieved. Cheng et al [ 39 ] demonstrated that two graphene layers in sliding commensurate contact, which are subjected to an isotropic, in-plane, synchronous strain, induce superlubric behavior.…”
Section: Mechanics Of Superlubricitymentioning
confidence: 99%
“…5,6 In recent decades, the realm of exploring superlubricity in both solids and liquids has garnered significant interest in the fields of fundamental science and engineering, thus, witnessing significant strides. For solid lubrication materials, such as MoS 2 , 7 graphene, 8 hexagonal boron nitride, 9 and diamond-like amorphous carbon coatings, 10 the realization of superlubrication required some strict conditions such as the incommensurate contact state, the protection of inert gases, or an ultrahigh vacuum condition, which limited its application. 11−13 To date, liquid superlubrication systems can be divided into water-and acid-based solutions, hydrated materials, ionic liquids, 2D materials as lubricant additives, and oil-based lubrication materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since it can decrease resistance and save energy, materials with superlubricity are of tremendous importance from the perspective of saving energy and protecting the environment. , In recent decades, the realm of exploring superlubricity in both solids and liquids has garnered significant interest in the fields of fundamental science and engineering, thus, witnessing significant strides. For solid lubrication materials, such as MoS 2 , graphene, hexagonal boron nitride, and diamond-like amorphous carbon coatings, the realization of superlubrication required some strict conditions such as the incommensurate contact state, the protection of inert gases, or an ultrahigh vacuum condition, which limited its application. …”
Section: Introductionmentioning
confidence: 99%
“…5,6 When COF < 0.01, it is usually considered to be a superlubricant. 7 After decades of experimental and theoretical research and development, superlubricants can be broadly categorized into two types: solid (e.g., typical graphite/ graphene, 8,9 molybdenum disulfide, 10 surface coatings, 11,12 etc.) and liquid (e.g., water/acid−based lubricants, 13,14 ionic liquids, 15−17 polyol liquids, 18 etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of superlubricity (i.e., the theoretical state of zero friction), which has been predicted and proposed since the 1990s, has ignited hope for addressing these concerns. , When COF < 0.01, it is usually considered to be a superlubricant . After decades of experimental and theoretical research and development, superlubricants can be broadly categorized into two types: solid (e.g., typical graphite/graphene, , molybdenum disulfide, surface coatings, , etc.) and liquid (e.g., water/acid–based lubricants, , ionic liquids, polyol liquids, etc.).…”
Section: Introductionmentioning
confidence: 99%